New anionic cobalt(III) complexes enable enantioselective synthesis of spiro-fused oxazoline and iodoacetal derivatives - Salem, Mohamed S. H.; Takizawa, Shinobu (Frontiers in Chemistry, 2022)
Anionic salicylimine-based cobalt (III) complexes featuring chiral ligands derived from isoleucine amino acids were used as efficient bifunctional phase-transfer catalysts for electrophilic iodination of enol ethers. The Brønsted acids of these complexes enabled the enantioselective asymmetric iodocyclization of enol ethers, furnishing spiro-fused oxazoline derivatives in high yields with up to 90:10 er. In addition, chiral cobalt (III) complexes catalyze the asymmetric intermolecular iodoacetalization of enol ethers with various alcohols to afford 3-iodoacetal derivatives in high yields with up to 92:8 er.